CYBER SECURITY IN SMALL AND MEDIUM ENTERPRISES (SMEs): WHAT’S GOOD OR BAD? (Journal of Governance and Development (JGD), 2022)
The Fourth Industrial Revolution (IR4.0) has provided immense benefits for the sustainability of businesses, with many businessesutilising websites to sell their products and services internationally. Cybersecurity has nonetheless emerged as one of the most significant global challenges posed by this new digitization trend. Currently, more than sixty percent of commercial transactions are conducted online or via digital wallets, necessitating exceptional security for transparent and secure transactions. Individuals are unable to maintain the security of their private data because of these evolving technologies, and cybercrime is on the rise. Information security is one of the most complex issues currently. Cybercrimes, which are increasing at an alarming rate, are the first thing that comes to mind when we think about cyber security. Consequently, numerous governments and corporations are enhancing their cybersecurity tools to combat cybercrime. Despite numerous precautions, cyber threats remain a major concern not only for government and large businesses, but also for Small and Medium-Sized Businesses (SMEs) companies. This paper examines the challenges and solutions faced by small and medium-sized enterprises (SMEs) in relation to cyber security issues. In addition, it also examines the Malaysian context that may hinder the cybersecurity adoption gap for risk mitigation and high security in operational and development business environments.